Political Union: Legitimacy and Efficiency to Overcome the Crisis. Issue 2 (December 2013) - Chopin, Thierry
This paper aims to outline a number of concrete proposals in view of providing detailed operational content for the project to create a genuine European political leadership and to strengthen legitimacy and democratic control of the decision-making process. The legal feasibility of each of the proposals set out here is analysed by identifying the type of reform it involves: innovation, using the treaty as it stands; limited changes to the Treaty under the simplified revision procedure; and more important changes to the Treaty under the ordinary revision procedure.